Reductive C-C coupling by desulfurizing gold-catalyzed photoreactions - Zhang, Lumin; Si, Xiaojia; Yang, Yangyang; Witzel, Sina; Sekine, Kohei; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (ACS catalysis, 2019)
[Au2(μ-dppm)2]Cl2-mediated photocatalysis reactions are usually initiated by ultraviolet A (UVA) light; herein, an unreported system using blue light-emitting diodes (LEDs) as excitation light source was found. The red shift of the absorption wavelength originates from the combination of [Au2(μ-dppm)2]Cl2 and ligand (Ph3P or mercaptan). On the basis of this finding, a gold-catalyzed reductive desulfurizing C-C coupling of electrophilic radicals and styrenes mediated by blue LEDs is presented, a coupling which cannot be efficiently accessed by previously reported methods. This mild and highly efficient C-C bond formation strategy uses mercaptans both as electron-deficient alkyl radical precursor as well as the hydrogen source. Two examples of amino acids have also been modified by using this strategy. Moreover, this methodology could be applied in polymer synthesis. Gram-scale synthesis and mechanistic insights into this transformation are also presented.